2005
DOI: 10.11606/issn.1678-4456.bjvras.2005.26423
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre os efeitos da associação gelatina-resorcina-formaldeído e do n-butil-2-cianoacrilato na síntese do parênquima hepático de coelhos

Abstract: Considerando-se as particularidades anatômicas e funcionais do fígado e a dificuldade da realização de procedimentos cirúrgicos eficientes quanto a hemostasia, estudou-se comparativamente os efeitos de dois adesivos cirúrgicos, gelatina-resorsina-formaldeído e n-butil-2-cianoacrilato, como métodos auxiliares na síntese do órgão. A metodologia utilizada determinou rigoroso acompanhamento clínico dos animais estudados, assim como realização de análises macro e microscópica de feridas cirúrgicas experimentalmente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…They reported that the time taken for hemostasis was similar, but that the injuries treated with fibrin showed signs of better regeneration and those treated with cyanoacrylate had a better reaction in terms of foreign body. Silveira et al 13 compared the application of n-butyl-2-cyanoacrylate with gelatineresorcine-formaldehyde and observed that both were efficient in achieving hemostasis although the cyanoacrylate showed more significant cellular and tissue alterations. What was inconvenient about cyanoacrylate is that the bleeding accelerates rapid polymerization and solidification and he risk of adhering to the material and its overflow leads to the formation of firm adherence with other structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that the time taken for hemostasis was similar, but that the injuries treated with fibrin showed signs of better regeneration and those treated with cyanoacrylate had a better reaction in terms of foreign body. Silveira et al 13 compared the application of n-butyl-2-cyanoacrylate with gelatineresorcine-formaldehyde and observed that both were efficient in achieving hemostasis although the cyanoacrylate showed more significant cellular and tissue alterations. What was inconvenient about cyanoacrylate is that the bleeding accelerates rapid polymerization and solidification and he risk of adhering to the material and its overflow leads to the formation of firm adherence with other structures.…”
Section: Discussionmentioning
confidence: 99%
“…This ideal adhesive must not alter the healing process, nor should it have side effects or carcinogenic agents 4 . Many hemostatic agents have been researched and different types and compositions of agents have been developed, among them fibrin adhesive [5][6][7][8][9][10][11][12] , cyanoacrylate 11,13,14 , gelatineresorcine 13,15,16 and oxidized cellulose 17 . Recently microporous polysaccharide hemispheres (MPH) arrived on the market, constituting spherical particles of controlled porosity obtained from bioinert vegetable polysaccharides and facilitates hemostasis through rapid absorption of the fluid in the blood, accelerating the aggregation of the plaques and clotting 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 1,000 patients suffering from liver trauma led by Feliciano et al between 1979 and, the mortality rate found was 10% 22 , and in another study, The presence of foreign body inflammatory reaction found in the histological analysis of the rats' livers treated with the collagen adhesive associated with fibrinogen and thrombin was similar to changes found in studies using fibrin glue in rats 24 , fibrin glue in rabbits 21 and polyglycolic acid mesh in pigs 25 . We did not observe histological findings suggestive of liver tissue necrosis or vacuolar degeneration, as described with the use of cyanoacrylate 26 , or the presence of abscesses near the adhesive application areas. The intense collagen deposition identified close to the adhesive application areas (Figure 5) is an important fact, if we consider that collagen is essential for the injured tissue repair process 24 .…”
Section: Discussionmentioning
confidence: 47%
“…In another study conducted by Saaiq Michelino Collagen, fibrinogen and thrombin biological addesive is effective in treating experimental liver injuries with fibrinogen and thrombin was similar to changes found in studies using fibrin glue in rats 24 , fibrin glue in rabbits 21 and polyglycolic acid mesh in pigs 25 . We did not find histological findings suggestive of necrosis of the liver tissue or vacuolar degeneration, as described with the use of cyanoacrylate 26 , or abscesses near the adhesive areas. The intense collagen deposition near identified the adhesive use areas (Figure 3) is an important fact, if we consider that collagen is essential for the injured tissue repair process 24 .…”
Section: Histological Changesmentioning
confidence: 40%